Analisis Peran Notaris Dalam Mencegah Tindak Pidana Pemalsuan Terhadap Akta Autentik - Firman Sjah; Mahsun Ismail; Khairul Umam; Salsabila Lina Rahman; Nur Rizkiyani Hafifah (Mahesa Research Center, 2026)
This paper aims to analyze the role of notaries in preventing criminal acts of forgery in notarial deeds, which often cause problems for the parties involved. This study focuses on the role and responsibilities of notaries in preventing criminal acts of forgery in notarial deeds and the mechanisms of supervision and law enforcement that can strengthen preventive functions in order to maintain the certainty and validity of notarial deeds. The research method used is normative research with a regulatory approach. The legal materials used were collected through literature study and analyzed descriptively and analytically. The results of the study show that, first, the role and responsibility of notaries in preventing criminal acts of forgery in notarial deeds can be carried out by verifying the identity and validity of the parties and ensuring the legality and legal compliance of each legal action. Second, supervision is necessary to minimize forgery committed by the parties, including the notary himself, as follows: strengthening supervision, awareness and guidance, use of technology, coordination and cooperation, law enforcement and strict sanctions for parties involved in forging notarial deeds, and public education to provide a comprehensive understanding of the importance of the validity and security of deeds.